PENINGKATAN AKTIVITAS DAN KETUNTASAN BELAJAR KOMPETENSI DASAR MENDESKRIPSIKAN RUMAH SEHAT MATA PELAJARAN ILMU PENGETAHUAN SOSIAL MENGGUNAKAN MODEL PEMBELAJARAN KONSTRUKTIVISME BAGI PESERTA DIDIK KELAS I DI SEKOLAH DASAR NEGERI 1 SUKARAME BANDAR LAMPUNG - Suryati, Anizar (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to investigate the incresing of activity and completeness of describing the healty house in social civil subject for the first grade students of SD Negeri 1 Sukarame in the academic year of 2013/2014. This study is classroom action research. The participants come from the first grade students of SD Negeri 1 Sukarame Bandar Lampung. To increase the activeness of participants related to the material taught, constructivism model is used in increasing the quality of study. It is very useful for the students in learning civil subject. Based on the research finding, it is known that the effectiveness of constructivism model cadevelop the participants to study and to do in critical thinking.